2019
DOI: 10.1002/pon.5068
|View full text |Cite
|
Sign up to set email alerts
|

Attachment styles, self‐compassion, and psychological adjustment in long‐term breast cancer survivors

Abstract: Objective: The increasing numbers of breast cancer survivors highlight the importance of delineating factors that identify women who are at risk of poor psychological adjustment in the long term. In breast cancer survivors, higher attachment anxiety and attachment avoidance have been associated with poorer psychological adjustment. Moreover, there is evidence that self-compassion, a kind manner of treating oneself during difficulties, is associated with psychological adjustment in this population. This study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 38 publications
4
33
0
Order By: Relevance
“…Studies in the context of chronic diseases such as cancer have demonstrated that attachment styles can predict psychological adjustment and well-being (Schmidt et al, 2002;Turner-Cobb et al, 2002;Hamama-Raz and Solomon, 2006;Porter et al, 2012;Vehling et al, 2019). It has been shown that attachment anxiety leads to higher psychological distress and increased levels of endocrine stress responses (Ehrenthal et al, 2011;Arambasic et al, 2019). Individuals with higher levels of attachment avoidance usually report lower levels of psychological burden than individuals with higher scores of attachment anxiety (Dozier and Lee, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in the context of chronic diseases such as cancer have demonstrated that attachment styles can predict psychological adjustment and well-being (Schmidt et al, 2002;Turner-Cobb et al, 2002;Hamama-Raz and Solomon, 2006;Porter et al, 2012;Vehling et al, 2019). It has been shown that attachment anxiety leads to higher psychological distress and increased levels of endocrine stress responses (Ehrenthal et al, 2011;Arambasic et al, 2019). Individuals with higher levels of attachment avoidance usually report lower levels of psychological burden than individuals with higher scores of attachment anxiety (Dozier and Lee, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with higher levels of attachment avoidance usually report lower levels of psychological burden than individuals with higher scores of attachment anxiety (Dozier and Lee, 1995). In patients with cancer, insecurely attached individuals use less active and less positive coping strategies to manage their diagnosis of cancer and survivorship issues, such as physical and emotional consequences of the cancer treatment (Schmidt et al, 2012;Arambasic et al, 2019;Romeo et al, 2019). Moreover, related studies have shown that attachment anxiety is associated with depression (Hunter et al, 2006;Porter et al, 2012;Nissen, 2016;Scheffold et al, 2017), higher symptoms of anxiety and reduced social well-being and quality of life among cancer patients (Porter et al, 2012;Smith et al, 2018;Arambasic et al, 2019;Romeo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a literature review by Sirois and Rowse, self-compassion is in connection with adaptive coping, lower stress and distress, and the practice of important health behaviors in chronic illness populations (20). Arambasic et al in their study concluded that self-compassion training may be useful for enhancing psychological adjustment in long-term breast cancer survivors (21). In other words, self-compassion can help chronic patients, especially cancer patients, to maintain their mental health and thus, their general health, more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Eight articles were further excluded, for reasons shown in the Appendix section ( Figure 1). Finally, 19 articles (n=2,713 patients, of which 73.3% were females) met our eligibility criteria and were included in this systematic review [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. The baseline characteristics of the included studies are comprehensively described in Table 1.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%